Analysis on the Shear Stress Propagation Mechanism in the Rock Reinforcement System - Chen, Jianhang; Li, Hui; Zhao, Shankun; Zhao, Hongbao; Zhang, Cun; Zhang, Junwen; Li, Danqi (Frontiers in Earth Science, 2022)
Rock reinforcement is significant in maintaining the stability of excavated structures, such as tunnels and underground roadways. However, shear failure in the rock reinforcement system, especially the shear failure at the rock reinforcement bolt surface, induces a threat to the rock reinforcement system. To reveal the shear stress (SS) propagation mechanism in the rock reinforcement system, this paper conducted a literature review. First, the investigation approaches that were used by previous researchers to study the SS propagation were summarized. The advantages and disadvantages of experimental tests, analytical simulation and numerical simulation were compared and analyzed. Then, the SS propagation process in the rock reinforcement system was presented. Two typical SS propagation modes were explained. More attention was given to the SS propagation mode in which the maximum SS propagates from the external end of rock reinforcement bolts to the internal end of rock reinforcement bolts. After that, a discussion section was given. In the discussion section, the significance of the SS propagation was further emphasized. Moreover, the limitations in analytical simulation and numerical simulation were indicated. It is concluded that when studying the SS propagation mechanism of rock reinforcement bolts, combing experimental tests, analytical simulation and numerical simulation is a better choice. This study is beneficial for revealing the SS propagation mechanism of the rock reinforcement system.